Meaningful use stage 2 e-prescribing threshold and adverse drug events in the Medicare Part D population with diabetes. (5th May 2015) - Powers, Christopher; Gabriel, Meghan Hufstader; Encinosa, William; Mostashari, Farzad; Bynum, Julie
Abstract: Evidence supports the potential for e-prescribing to reduce the incidence of adverse drug events (ADEs) in hospital-based studies, but studies in the ambulatory setting have not used occurrence of ADE as their outcome. Using the "prescription origin code" in 2011 Medicare Part D prescription drug events files, the authors investigate whether physicians who meet the meaningful use stage 2 threshold for e-prescribing (≥50% of prescriptions e-prescribed) have lower rates of ADEs among their diabetic patients. Risk of any patient with diabetes in the provider's panel having an ADE from anti-diabetic medications was modeled adjusted for prescriber and patient panel characteristics. Physician e-prescribing to Medicare beneficiaries was associated with reduced risk of ADEs among their diabetes patients (Odds Ratio: 0.95; 95% CI, 0.94-0.96), as were several prescriber and panel characteristics. However, these physicians treated fewer patients from disadvantaged populations.